Method for preparing neutron and gamma ray double-shielding absorption composite material through SLM technology
Through the Gd2O3/W/AlSi10Mg composite material prepared using SLM technology in spent fuel storage and transportation, the problem of difficult to achieve neutron and gamma ray dual shielding in the prior art is solved, and efficient radiation shielding and excellent mechanics are achieved. performance.
Patent Information
- Application Number
- CN202411720745.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to effectively realize the double shielding of neutron and gamma rays, and traditional materials lack heat resistance and radiation resistance in spent fuel storage and transportation.
Selected laser melting (SLM) technology is used to combine aluminum alloy powder, tungsten powder and gadolinium oxide powder to prepare Gd2O3/W/AlSi10Mg composite material to achieve double shielding of neutrons and gamma rays.
This composite material not only has efficient neutron and gamma ray shielding performance, but also has excellent mechanical properties and high density, meeting the needs of integrated structural and functional design.
Smart Images

Figure CN119489205A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a neutron and gamma ray double shielding absorption composite material by utilizing SLM technology, and belongs to the technical preparation field of metal-based composite materials. Background Art
[0002] With the rapid development of my country's nuclear power industry, the amount of spent fuel unloaded is increasing year by year, and the storage of spent fuel has become a problem that my country urgently needs to solve. The unloaded spent fuel still has strong radioactivity and will produce a large amount of radioactive radiation, such as α rays, β rays, γ rays, neutron radiation, etc. Since α rays and β rays have low penetration and are easily absorbed, they can be completely blocked by using materials with extremely small thickness, making it easier to shield them; while neutron radiation is electrically neutral and has strong penetration, and γ rays have ionizing properties and are harmful to living cells and tissues. Therefore, among these radiations, neutron radiation and γ rays are the most harmful to the human body and the environment. Gadolinium oxide will emit secondary gamma rays while absorbing neutrons, so it is difficult to achieve the required structural and functional integration with traditional, single shielding materials. Therefore, it is urgent to develop a double shielding absorption material with good neutron and gamma ray absorption performance and structural and functional integrated design.
[0003] Nuclear radiation shielding materials have been around and used for many years. Currently, materials used for neutron absorption include high-boron steel, boron-containing polyethylene, B4C / Al, cadmium plates, etc.; materials used for gamma-ray shielding include iron-based materials, lead-containing resins, concrete, etc. Due to the low boron content in high-boron steel, it is impossible to achieve good neutron shielding, and boron is prone to produce brittle continuous network boride in steel, which significantly reduces the toughness of the material; boron-containing polyethylene has good neutron moderation and absorption capabilities, but poor heat resistance and radiation resistance, and cannot serve for a long time in the harsh environment of spent fuel storage and transportation; the high content of boron carbide in B4C / Al makes the mechanical properties of the composite material worse; metallic cadmium is toxic and has secondary gamma rays. Iron-based materials have poor corrosion resistance and mechanical properties and a large specific gravity; lead in lead-containing resins is toxic and harmful to the human body; concrete is bulky and difficult to move, and cannot be used for shielding protection of mobile nuclear reactors, and its shielding effect on neutrons and gamma rays is also relatively poor. Therefore, in response to the increasingly harsh physical environment and complex radiation environment in modern radiation protection scenarios, the prepared shielding composite materials need not only to have dual shielding performance for neutrons and gamma rays, but also to have excellent thermodynamic properties; in addition, the materials in the structural components of related nuclear facilities also need to have excellent high temperature resistance and radiation resistance. Therefore, it is difficult to meet the above stringent requirements by adding a single functional filler to metal matrix materials such as stainless steel and aluminum alloy. Therefore, according to different application scenarios and requirements, it is currently a hot topic to dope two or more functional fillers in metal matrix materials to prepare composite materials with excellent shielding performance, excellent thermodynamic properties and high radiation resistance service life. There are many processes for preparing neutron and gamma ray dual shielding composite materials, such as powder metallurgy process, stirring casting process, vacuum hot pressing process, extrusion casting process, spark plasma sintering process, etc. Each method has its own characteristics, such as severe interface reaction of casting materials, complex preparation process of powder metallurgy method, expensive mold of spark plasma sintering method, and long production cycle. Summary of the invention
[0004] In order to solve the shortcomings and deficiencies of traditional preparation methods and single-function fillers, and to meet the needs of spent fuel treatment for neutron and gamma-ray dual-shielding materials with integrated functional and structural design, the present invention aims to provide a new design and preparation method for neutron and gamma-ray dual-shielding composite materials. While meeting the dual shielding functions of neutrons and gamma rays in spent fuel treatment, the composite material also adopts SLM technology to make the material low in processing cost and have good mechanical properties, meeting the needs of structural and functional integrated design.
[0005] The neutron and gamma ray dual shielding absorption composite material of the present invention is prepared from the following raw materials in percentage by mass: W: 15.00wt.%, Gd2O3: 5.00wt.%, AlSi10Mg: 80.00wt.%.
[0006] The composite material can meet the requirements of dual shielding of neutrons and gamma rays.
[0007] The method for preparing a neutron and gamma ray double shielding absorption composite material by SLM technology described in the present invention comprises the following steps: (1) According to the designed composition ratio, AlSi10Mg powder with a particle size of 15-45 μm, W powder with a particle size of 3-5 μm, and Gd2O3 powder with a particle size of 8-10 μm are selected as raw materials; (2) AlSi10Mg powder, W powder and Gd2O3 powder were placed in an omnidirectional ball mill under argon protection gas and uniformly mixed to prepare Gd2O3 / W / AlSi10Mg mixed powder; (3) Drying the obtained mixed powder in a vacuum drying oven for 2 to 5 hours to obtain a pretreated Gd2O3 / W / AlSi10Mg mixed powder; (4) Preheating the pretreated mixed powder and the aluminum alloy substrate to 200°C, and then air cooling to 60°C; (5) Using the mixed powder as the raw material for selective laser melting, the mixed powder is loaded into the powder supply cylinder of the SLM forming equipment; (6) Clean the aluminum alloy substrate with an aluminum alloy cleaning agent, then wipe the substrate with 99% anhydrous ethanol and dry it; (7) Slice and layer the constructed three-dimensional model of the component according to the thickness of the powder layer, and then transmit the two-dimensional contour information of each layer to the computer; (8) During SLM forming, the automatic powder spreading system first spreads the mixed powder in the powder supply cylinder onto the base of the forming cylinder in sequence according to the thickness of the powder spreading layer. The high-energy laser beam scans the mixed powder, and then the powder spreading and laser scanning steps are repeated until all the mixed powder in the powder supply cylinder is spread into the forming cylinder and the forming is completed, thereby preparing the following Figure 2 The shown Gd2O3 / W / AlSi10Mg composite material has uniform particle dispersion and good interface connection.
[0008] The present invention utilizes SLM technology, which has the ability of rapid prototyping, greatly improving production efficiency; by using precise control of the laser beam, high-precision and high-quality manufacturing of parts can be achieved, and parts with complex shapes and structures can be prepared; and the SLM molding process has an extremely fast cooling speed, and is easy to form a fine-grained structure, which is beneficial to improving the mechanical properties of the prepared material.
[0009] Then the color, morphology, microstructure, microhardness and neutron absorption rate of the new Gd2O3 / W / AlSi10Mg neutron and gamma ray dual shielding absorption composite material were tested, analyzed and characterized; Use neutron and gamma ray flux rate meters to detect and analyze neutron and gamma ray absorption rates; Use electron microscope and scanning electron microscope to analyze metallographic structure and microstructure morphology; Microhardness analysis was performed using a microhardness tester; The bending and tensile strength analysis was carried out using a universal tensile testing machine.
[0010] Furthermore, in the step (2), the ball-to-material ratio in the ball milling process is 3:1, the ball milling speed is 200 rpm, and the ball milling time is 4 hours; Furthermore, in step (8), a strip scanning strategy is adopted, the angle between two adjacent scanning lines is 67°, the laser wavelength is 1060-1080 nm, the laser spot size D=50 μm, the scanning speed V=500-2500 mm / s, the scanning spacing is 20-80 μm, the laser scanning power is 100-500 W, and the layer thickness is 30 μm.
[0011] The present invention adopts the selective laser melting (SLM) technology to produce a composite material with good density for dual absorption of neutrons and gamma rays through melting and forming. The density of the composite material can reach more than 98%, the neutron shielding rate can reach 99%, and the gamma ray attenuation coefficient meets the requirements of gamma ray shielding. In addition, the composite material also has good mechanical properties.
[0012] The advantages of the present invention are: Compared with the background technology, the present invention has obvious advantages. It is aimed at the needs of neutron radiation and gamma ray shielding protection in the storage and transportation of spent fuel in nuclear power plants, and prepares a composite material with dual shielding absorption of neutrons and gamma rays. The neutron and gamma ray dual shielding composite material is prepared by mixing aluminum alloy powder, tungsten powder and gadolinium oxide powder, and selective laser melting (SLM) technology. Not only the shielding performance of thermal neutrons and gamma rays is improved, but also the mechanical properties of the Gd2O3 / W / AlSi10Mg composite material are significantly improved. And the density of the composite material reaches more than 98%. The tensile stress of the Gd2O3 / W / AlSi10Mg composite material prepared by using 15.00wt.% W powder, 5.00wt.% Gd2O3 powder, and 80.00wt.% AlSi10Mg powder can reach 190MPa and the yield strength is 110MPa. This preparation method has advanced and reasonable process, accurate and detailed parameters, and is a new preparation method for neutron and gamma ray dual shielding composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a preparation flow chart of the neutron and gamma ray double shielding absorption composite material of the present invention; Figure 2 These are OM micrographs and SEM micrographs of the neutron and gamma ray dual shielding absorption composite material of the present invention; wherein a is an OM micrograph and b is an SEM micrograph; Figure 3 It is a line scanning energy spectrum of the neutron and gamma ray double shielding absorption composite material of the present invention; Figure 4 It is a schematic diagram of the tensile properties of the neutron and gamma ray double shielding absorption composite material of the present invention; Figure 5 It is a schematic diagram of component proportion simulation of the neutron and gamma ray double shielding absorption composite material of the present invention, wherein a is a neutron shielding simulation diagram, and b is a gamma ray attenuation multiple diagram. DETAILED DESCRIPTION
[0014] Selective laser melting (SLM) technology is an important new additive manufacturing technology in recent years. It is improved on the basis of selective laser sintering (SLS) technology and can meet the needs of personalized customization of complex structural parts. This technology shortens the time of product development through the intervention of simulation software; due to the reuse of raw materials, the production cost is significantly reduced; and the precise control of the laser beam realizes the homogenization of the structure and organization of the molding material and the excellence of the mechanical properties. SLM technology has significant advantages in aerospace, medical and national defense and military industries and has made great progress. Based on these advantages, SLM technology has received widespread attention and developed rapidly in recent years, becoming the focus of research at home and abroad. Aiming at the needs of structural and functional integrated neutron and gamma ray double shielding absorption materials, the present invention adopts selective laser melting (SLM) technology, uses AlSi10Mg powder, Gd2O3 powder and W powder as raw materials, and prepares neutron and gamma double shielding absorption composite materials with excellent performance through grinding and printing.
[0015] The specific implementation modes of the present invention are described in detail below with reference to the accompanying drawings.
[0016] Example 1 This example is a method for preparing a neutron and gamma ray double shielding hand washing composite material, such as Figure 1 As shown, the following steps are included: (1) According to the designed composition ratio, 360 g of AlSi10Mg powder with a particle size of 15-45 μm, 67.5 g of W powder with a particle size of 3-5 μm, and 22.5 g of Gd2O3 powder with a particle size of 8-10 μm were selected as raw materials; (2) AlSi10Mg powder, W powder and Gd2O3 powder were placed together in an omnidirectional ball mill under argon protection gas, and uniformly mixed at a ball-to-material ratio of 3:1, a ball milling speed of 200 rpm, and a ball milling time of 4 h to prepare a Gd2O3 / W / AlSi10Mg mixed powder; (3) drying the obtained mixed powder in a vacuum drying oven for 2 h to obtain a pretreated Gd2O3 / W / AlSi10Mg mixed powder; (4) Preheating the pretreated mixed powder and the aluminum alloy substrate to 200°C, and then air cooling to 60°C; (5) Using the mixed powder as the raw material for selective laser melting, the mixed powder is loaded into the powder supply cylinder of the SLM forming equipment; (6) Clean the aluminum alloy substrate with an aluminum alloy cleaning agent, then wipe the substrate with 99% anhydrous ethanol and dry it; (7) Slice and layer the constructed three-dimensional model of the component according to the thickness of the powder layer, and then transfer the two-dimensional contour information of each layer to the computer; (8) A strip scanning strategy was adopted, with the angle between two adjacent layers of scanning lines being 67°, the laser spot size being D = 50 μm, the scanning speed being V = 1400 mm / s, and the scanning spacing being 60 μm; the laser scanning power being 200 W, and the layer thickness being 30 μm; (9) During SLM forming, the automatic powder spreading system first spreads the mixed powder in the powder supply cylinder onto the base of the forming cylinder in sequence according to the thickness of the powder layer. The high-energy laser beam scans the mixed powder, and then the steps of powder spreading and laser scanning are repeated until all the mixed powder in the powder supply cylinder is spread into the forming cylinder and the forming is completed, thereby preparing a Gd2O3 / W / AlSi10Mg composite material with uniform particle dispersion and good interface connection.
[0017] Example 2 This example provides a method for preparing a neutron and gamma ray dual shielding absorption composite material, such as Figure 1 As shown, the following steps are included: (1) According to the designed composition ratio, 360 g of AlSi10Mg powder with a particle size of 15-45 μm, 67.5 g of W powder with a particle size of 3-5 μm, and 22.5 g of Gd2O3 powder with a particle size of 8-10 μm were selected as raw materials; (2) AlSi10Mg powder, W powder and Gd2O3 powder were placed together in an omnidirectional ball mill under argon protection gas, and uniformly mixed at a ball-to-material ratio of 3:1, a ball milling speed of 200 rpm, and a ball milling time of 4 h to prepare a Gd2O3 / W / AlSi10Mg mixed powder; (3) drying the obtained mixed powder in a vacuum drying oven for 2 h to obtain a pretreated Gd2O3 / W / AlSi10Mg mixed powder; (4) Preheating the pretreated mixed powder and the aluminum alloy substrate to 200°C, and then air cooling to 60°C; (5) Using the mixed powder as the raw material for selective laser melting, the mixed powder is loaded into the powder supply cylinder of the SLM forming equipment; (6) Clean the aluminum alloy substrate with an aluminum alloy cleaning agent, then wipe the substrate with 99% anhydrous ethanol and dry it; (7) Slice and layer the constructed three-dimensional model of the component according to the thickness of the powder layer, and then transfer the two-dimensional contour information of each layer to the computer; (8) A strip scanning strategy was adopted, the angle between two adjacent scanning lines was 67°, the laser spot size was D = 50 μm, the scanning speed was V = 1937 mm / s, and the scanning interval was 60 μm; when the laser scanned the mixed powder: the power was 300 W and the layer thickness was 30 μm; (9) During SLM forming, first, the automatic powder spreading system spreads the mixed powder in the powder supply cylinder onto the base of the forming cylinder in sequence according to the thickness of the powder layer. The high-energy laser beam scans the mixed powder, and then the steps of powder spreading and laser scanning are repeated until all the mixed powder in the powder supply cylinder is spread into the forming cylinder and the forming is completed, thereby preparing a Gd2O3 / W / AlSi10Mg composite material with uniform particle dispersion and good interface connection.
[0018] Example 3 This example prepares a novel neutron and gamma ray dual shielding absorption composite material. Figure 1 As shown, the following steps are included: (1) According to the designed composition ratio, 360 g of AlSi10Mg powder with a particle size of 15-45 μm, 67.5 g of W powder with a particle size of 3-5 μm, and 22.5 g of Gd2O3 powder with a particle size of 8-10 μm were selected as raw materials; (2) AlSi10Mg powder, W powder and Gd2O3 powder were placed together in an omnidirectional ball mill under argon protection gas, and uniformly mixed at a ball-to-material ratio of 3:1, a ball milling speed of 200 rpm, and a ball milling time of 4 h to prepare a Gd2O3 / W / AlSi10Mg mixed powder; (3) drying the obtained mixed powder in a vacuum drying oven for 2 h to obtain a pretreated Gd2O3 / W / AlSi10Mg mixed powder; (4) Preheating the pretreated mixed powder and the aluminum alloy substrate to 200°C, and then air cooling to 60°C; (5) Using the mixed powder as the raw material for selective laser melting, the mixed powder is loaded into the powder supply cylinder of the SLM forming equipment; (6) Clean the aluminum alloy substrate with an aluminum alloy cleaning agent, then wipe the substrate with 99% anhydrous ethanol and dry it; (7) Slice and layer the constructed three-dimensional model of the component according to the thickness of the powder layer, and then transfer the two-dimensional contour information of each layer to the computer; (8) A strip scanning strategy was adopted, the angle between two adjacent scanning lines was 67°, the laser spot size was D = 50 μm, the scanning speed was V = 1106 mm / s, and the scanning interval was 40 μm; when the laser scanned the mixed powder: the power was 300 W and the layer thickness was 30 μm; (9) During SLM forming, first, the automatic powder spreading system spreads the mixed powder in the powder supply cylinder onto the base of the forming cylinder in sequence according to the thickness of the powder layer. The high-energy laser beam scans the mixed powder, and then the steps of powder spreading and laser scanning are repeated until all the mixed powder in the powder supply cylinder is spread into the forming cylinder and the forming is completed, thereby preparing a Gd2O3 / W / AlSi10Mg composite material with uniform particle dispersion and good interface connection.
[0019] The above-mentioned embodiments are only descriptions of the preferred implementation of the present invention, and the preferred embodiments do not describe all details in detail, nor do they limit the invention to the specific implementation. The present invention maintains the spirit of invention design, the invention content is detailed, creative and practical, and has important application value in related fields.
[0020] like Figure 2 As shown in the figure, the microstructure morphology of the Gd2O3 / W / AlSi10Mg neutron and gamma ray double shielding absorption composite material. In Figure a, it can be seen that the angle between the layers rotates by 67° during the laser printing process. In Figure b, it can be seen that the gadolinium oxide and tungsten particles are evenly distributed in the shape of crystal cells on the aluminum matrix.
[0021] like Figure 3 As shown, the line scanning energy spectrum of the Gd2O3 / W / AlSi10Mg neutron and gamma ray double shielding absorption composite material, it can be seen in the figure that the interface between the gadolinium oxide particles, tungsten particles and the aluminum matrix is well connected.
[0022] like Figure 4 As shown, a schematic diagram of the tensile properties of the Gd2O3 / W / AlSi10Mg neutron and gamma ray double shielding absorption composite material is shown in the figure: the tensile strength reaches 190MPa and the elongation is 2.4%, indicating that the prepared Gd2O3 / W / AlSi10Mg neutron and gamma ray double shielding absorption composite material has good mechanical properties.
[0023] like Figure 5As shown in the figure, a schematic diagram of the component ratio simulation of the Gd2O3 / W / AlSi10Mg neutron and gamma-ray dual shielding absorption composite material is shown. As shown in the figure: when the mass fraction of Gd2O3 reaches 5%, the neutron shielding rate remains almost unchanged; the gamma-ray attenuation multiple gradually increases with the increase of W content. Since the more W content, the more difficult it is to form the composite material, the mass fraction of W is selected as 15% after comprehensive evaluation, indicating that the prepared Gd2O3 / W / AlSi10Mg neutron and gamma-ray dual shielding absorption composite material has both good mechanical properties and a high shielding rate.
Claims
1. A neutron and gamma ray double shielding absorption composite material, characterized in that: The composite material is prepared from the following raw materials in percentage by weight: W: 15.00wt.%, Gd2O3: 5.00wt.%, AlSi10Mg: 80.00wt.%.
2. A method for preparing a neutron and gamma ray double shielding absorption composite material using SLM technology, characterized in that: The method comprises the following steps: (1) The neutron and gamma ray dual shielding absorption composite material according to claim 1 is prepared by selecting AlSi10Mg powder with a particle size of 15-45 μm, W powder with a particle size of 3-5 μm, and Gd2O3 powder with a particle size of 8-10 μm as raw materials in terms of mass percentage; (2) AlSi10Mg powder, W powder and Gd2O3 powder were placed in an omnidirectional ball mill under argon protection gas and uniformly mixed to prepare Gd2O3 / W / AlSi10Mg mixed powder; (3) Drying the obtained mixed powder in a vacuum drying oven for 2 to 5 hours to obtain a pretreated Gd2O3 / W / AlSi10Mg mixed powder; (4) Preheating the pretreated Gd2O3 / W / AlSi10Mg mixed powder and the aluminum alloy substrate to 200°C, and then air cooling to 60°C; (5) Using the mixed powder as the raw material for selective laser melting, the mixed powder is loaded into the powder supply cylinder of the SLM forming equipment; (6) Clean the aluminum alloy substrate with an aluminum alloy cleaning agent, then wipe the substrate with 99% anhydrous ethanol and dry it; (7) Slice and layer the constructed three-dimensional model of the component according to the thickness of the powder layer, and then transfer the two-dimensional contour information of each layer to the computer; (8) During SLM forming, the automatic powder spreading system first spreads the mixed powder in the powder supply cylinder onto the base plate of the forming cylinder in sequence according to the thickness of the powder spreading layer. The high-energy laser beam scans the mixed powder, and then the powder spreading and laser scanning steps are repeated until all the mixed powder in the powder supply cylinder is spread into the forming cylinder and the forming is completed, thereby preparing the Gd2O3 / W / AlSi10Mg composite material.
3. The method for preparing a neutron and gamma ray double shielding absorption composite material by SLM technology as claimed in claim 2, characterized in that: The ball-to-material ratio in the ball milling process in step (2) is 3:1, the ball milling speed is 200 rpm, and the ball milling time is 4 hours.
4. A method for preparing a neutron and gamma ray double shielding absorption composite material using SLM technology as claimed in claim 2 or 3, characterized in that: In the step (8), a strip scanning strategy is adopted, the angle between two adjacent scanning lines is 67°, the laser wavelength is 1060-1080 nm, the laser spot size D=50 μm, the scanning speed V=500-2500 mm / s, the scanning spacing is 20-80 μm; the laser scanning power is 100-500 W, and the layer thickness is 30 μm.